Sleep Quality Assessment and Its Predictors Among Patients at the Step-Down Room - Dwiningsih, Sri Utami; Bintari, Chindy Eti Tita; Sudiarto, Sudiarto; Hartoyo, Mugi (Poltekkes Kemenkes Semarang, 2024)
Background: critical patients often experience sleep disturbances, namely the time that is too short to sleep. Changes in the characteristics and sleep time of critical patients can cause worsening of the disease and increase the risk of death. Sleep in critical patients has a very important function in the repair mechanism of damaged tissue cells (natural healing mechanism).Purpose: to determine the relationship between disease response factors, environmental factors, and nursing procedure factors on the sleep quality of patientsMethods: this cross-sectional study took place at a tertiary hospital, from March to May 2023, including 50 adults. We collected demographic and clinical data and utilized the Richards-Campbell Sleep Questionnaire (RCSQ) and the Sleep Disorders Factors Questionnaire (KFGT) scale to evaluate sleep qualityResults: the study showed a significant relationship between physical factors and sleep quality in patients with sig. 0.001 (sig. <0.05) and shows a strong relationship (p value = 0.84). There is a significant relationship between environmental factors and the patient's sleep quality with a sig. 0.001 (sig. <0.05) and shows a very strong relationship with a p value of 0.77.Conclusion: the physical factors, environmental factors, and nursing pro These findings emphasize the importance of integrating sleep quality education into sleep management strategies.cedure factors are related to the quality of sleep of patients at the HCU RSUP Dr. Kariadi.